A dialogue of one: Reflection on visual practice through drawing. Issue 1 (1st January 2016) - Croft, Michael
This article concerns the reflection of the author on his visual practice. The author carried out a piece of work in the medium of drawing-based painting for this purpose. The work is on canvas and was situated in the right angle of two adjoining walls of a studio. The process was recorded visually using stop-motion photography, reference to stills of which are included at the end of the article. The author also spoke his thoughts into a voice recorder while drawing, the transcripts providing, as nearly as possible, subjective reflexive content for the author's more analytical reflection. Summaries of the transcripts are included in the article as well as some excerpts included as long-form captions alongside photographic images. The article involves questions of the author's own corporeal embodiment in the drawing, self-performance as a mode of content, and the author's individual working process as the work's narrative. Theoretical references are to phenomenology, philosophy of perception and some recent articles concerning research from a practice basis.